Mapping American Literature with The Great Gatsby - Cathryn Halverson (American Studies in Scandinavia)
Taking The Great Gatsby as its central case study, this essay discusses my method of teaching regional American literature in Nordic classrooms through a liberal use of maps. I argue that closely attending to the cities, states, and regions to which literary texts refer helps students better understand and scrutinize their larger claims.